The influences of marketing mix(7p), perceived quality, and product knowledge on consumer purchase intention of chinese domestic brands in mobile phones in fujian province, China - Wu, Xiaomin; Putachote, Nitipon (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3649, 2025)
Consumers' purchasing intentions heavily influence the scale of domestic brands in China's fiercely competitive smartphone market. This study examines the impact of the marketing mix (7Ps), perceived quality, and product knowledge on consumers' purchase intention for domestic mobile phone brands in Fujian. A quantitative survey was conducted with 400 consumers from urban and rural areas, and the data were analyzed using descriptive statistics, t-tests, one-way ANOVA, and multiple linear regression. Demographic factors such as age, education, income, occupation, work experience, and work location are found to have a significant influence on purchase intention, whereas gender, residency, and work position do not. Product, physical evidence, and price are the most predictive elements of the marketing mix. Perceived quality, especially responsiveness, empathy, and reliability, has a direct impact on purchase intention. Besides, product knowledge, as represented by the product life cycle, has the greatest impact on consumer decision-making. Seventy-five percent of the variability in purchase intention can be explained, pointing to the significance of the findings. These results offer valuable implications for local smartphone manufacturers: optimize their marketing strategies, improve perceived quality, and leverage consumer knowledge to reinforce market control.